Development of a tool to motivate for healthy behaviors to prevent dementia in Cuba, Puerto Rico and Dominican Republic. (31st December 2021) - Peeters, Geeske; Almirall‐Sanchez, Arianna; Llibre‐Guerra, Jorge J; Jiménez‐Velazquez, Ivonne Z; Acosta, Daisy M; Lawlor, Brian; Anne, Kenny Rose; Yaffe, Kristine; Llibre‐Rodriguez, Juan J
Abstract: Background: Previous research showed that up to 56% of all dementia cases in Latin America could potentially be prevented if all modifiable risk factors were eliminated. Trends of studies in Latin America show, however, that lifestyles are declining. In absence of a cure, prevention is crucial. The aim was to develop a tool that can be used in primary care settings to raise awareness for modifiable risk factors and motivate high‐risk individuals to adopt healthy lifestyles to reduce their risk of dementia. Method: Data were from the Cuban (n=1846, mean age=73.9 ±6.4), Dominican Republic (DR, n=1053, mean age=76.3 ±6.8) and Puerto Rican (PR, n=1166, mean age=76.3 ±7.4) cohorts of the 10/66 Dementia Research Group. Participants completed questionnaires, health examination and cognitive tests at baseline and on average 4.5‐5 years later. Logistic regression was used to identify key modifiable risk factors. The 3 or 4 most important modifiable risk factors were combined into a grid and cells were colour coded to display the levels of risk according to absolute proportions of incident dementia (green/low: <9%, yellow/medium: 9‐<13%, orange/high: 13‐<20%, red/very high: >20%). Result: Physical activity, hypertension and diet were identified as the key modifiable risk factors. Hence, the grid included hypertension (yes/no), diet (composite measure of regular/no fish consumption and <4/4+ serves of vegetables) and physical activity (high, moderate, low) only. The levels of risk varied from low (6.6%) in participants with none of the risk factors to high (18.5%) in participants with all three risk factors. The highest risk was found in participants who were inactive and did not eat fish (24.8%). Conclusion: We have developed a tool that visualises the levels of risk and how each risk factor contributes to the risk of dementia. It also shows how one may lower their risk by addressing the risk factors. The tool can be used in primary care settings to motivate people for adopting healthy behaviours.